Komunikasi Virtual melalui Perilaku Trash-Talking Antar Pemain Game Online Mobile Legends - Yasha Langitta Setiawan; Januardi Nasir; Roby Hadi Putra (Ekasakti Jurnal Penelitian dan Pengabdian)
The current digital era makes people tend to use online media rather than conventional media. Online games are media that are often used by people, one of which is the mobile legend game. The mobile legend game has a virtual community that is used in virtual communication using dirty words or known as trash talking. The phenomenon of trash talking behavior often occurs in online game players. This behavior involves the use of words that are intended to insult, brag, intimidate, or provoke other players. The purpose of this study was to determine virtual communication through trash talking behavior between online mobile legend game players with Alferd Schutz's phenomenological theory. This study used a qualitative method and data was taken through interviews and direct observation. The results of the study showed that the meaning of trash talking from the BSK squad community was negative, causing cyberbullying and disrupting the comfort of playing for other players. The experience of trash talking from mobile legend game players in the BSK squad community is an unpleasant experience from the emotional factors experienced by players, such as failure or defeat, which can trigger Trash-Talking behavior. The motives for trash talking behavior include as a strategy in playing games, the excitement of playing games, intimidation, and the habit of saying bad words in real life.